Factors Contributing to Low Teachers Competencies Score - Sabila Nahari; Mohammad Adnan Latief; Utari Praba Astuti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: Competent teachers contribute to the students’ achievement significantly. Therefore, the government established a teacher professional development program with various activities. The program aims to improve their teaching skills, professional knowledge, and teaching effectiveness. However, many teachers have low competency even after joining the teacher professional development program. The low teacher competency score can be seen from the result of the teacher competency test. This research uses a quantitative design to investigate factors that contribute to the teachers’ competence. The results show factors that contribute to the low teachers’ competence are not doing classroom action research and writing article, rarely attending seminars or workshop, never being a speaker at seminars, low frequency of maintaining their English skill, not understanding the rights, mechanism, implementation of teacher competency test, not understandingng the objective of teacher competency test as a condition job promotion, and the unreadiness of the teacher in taking the examination.Abstrak: Guru yang kompeten berkontribusi terhadap prestasi siswa secara signifikan. Oleh karena itu, pemerintah membentuk program pengembangan profesional guru dengan berbagai kegiatan. Program ini bertujuan untuk meningkatkan keterampilan mengajar, pengetahuan profesional, dan efektivitas pengajaran mereka. Namun, banyak guru memiliki kompetensi rendah bahkan setelah mengikuti program pengembangan profesional guru. Skor kompetensi guru yang rendah dapat dilihat dari hasil tes kompetensi guru. Penelitian ini menggunakan desain kuantitatif untuk menyelidiki faktor-faktor yang berkontribusi terhadap kompetensi guru. Hasil penelitian menunjukkan faktor-faktor yang berkontribusi terhadap rendahnya kompetensi guru adalah tidak terbiasa melakukan penelitian tindakan kelas dan menulis artikel, jarang menghadiri seminar atau lokakarya, tidak pernah menjadi pembicara di seminar, rendahnya frekuensi guru dalam mempertahankan keterampilan bahasa Inggris mereka, tidak memahami hak, mekanisme, pelaksanaan tes kompetensi guru, tidak memahami tujuan tes kompetensi guru sebagai syarat promosi pekerjaan, dan ketidaksiapan guru dalam mengikuti ujian.